Traumatic abdominal wall hernia after impact from handlebar: A case report - Kheng, Hooi Chan; Sentilnathan Subramaniam; Firdaus Hayati (Elsevier Ltd, 2021)
Traumatic abdominal wall hernia (TAWH) is a rare type of hernia resulting from blunt abdominal trauma. It develops following the inertia of sudden, high-energy blunt trauma or focused low energy impact. A 22-year-old motorcyclist presented to the emergency department following a collision with an automobile. Clinical examination demonstrated a bulging mass at the lower abdomen, resulting from impact with the motorcycle handlebar. A contrast-enhanced CT scan of the abdomen revealed a disruption of both rectus abdominis muscle and linea alba at the lower abdomen with loops of small bowels and mesentery herniating through the defect, associated with multiple air pockets and pneumoperitoneum. Exploratory laparotomy showed TAWH containing loops of small bowel and mesentery in addition to mesenteric tears. Small bowel resection with primary anastomosis and repair of the anterior abdominal wall defect using interrupted polypropylene sutures was performed. The patient recovered well postoperatively and was discharged home three days later. A follow-up at 1 year showed no evidence of recurrence.